Quadratically converging iterative schemes for nonlinear Volterra integral equations and an application. (1997) - Pandit, Sudhakar G.
Abstract : A generalized quasilinear technique is employed to derive iterative schemes for nonlinear Volterra integral equations under various monotonicity and convexity (concavity) conditions on the kernels. The iterates in the schemes are linear, and converge monotonically, uniformly and quadratically to the unique solution. An application to a boundary-layer theory problem and examples illustrating the results are presented.